The interconnections between the publications "Kazakh" and "Ak Zhol" - Koigeldieva З.Ж. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The beginning of the twentieth century is a period in the history of the Kazakh people with the most complex social and socio-political contradictions. The beginning of the century was marked by the formation of the National intelligent people, a very important innovation in the spiritual life of Kazakh society. The object of the study was publications aimed at preserving the country and the integrity of the nation in that difficult period.The article provides information about the history of the appearance of periodicals, which were published at the beginning of the twentieth century and became a beacon for Kazakh society. It is told about the periodicals “Kazakh” and “Ak Zhol” which united the Kazakh citizens, served in accordance with keeping the peoples’ national value among other periodicals. At the same period, the policy of the Tsarist authorities on the Kazakh land was sharply criticized by theKazakh intelligent people. The subject of our research is publications from a national point of view, which haveachieved their main goal as a driving force, preserving the integrity of the nation. In the article, we focused on the direction of the publications “Kazakh” and “Ak Zhol”, which became the basis of the Alash language. An extensive study of the topic covered by the newspaper in society was carriedout, focusing on articles published on various topics separately.If we compare the time of publication and the public environment of the two newspapers, we can say thatthe newspaper “Ak Zhol” was able to raise national political thought to a qualitatively new level in the new conditions, and we were convinced that the ideas raised in the newspaper “Kazakh” are actually going through a difficult period, facing the realities of the real life of Soviet society, in which the colonial power was strengthened in the activities of “Ak Zhol”. The scientific significance of the article is determined by the comparative study of published articles in the newspapers “Kazakh” and “Ak Zhol”.The research methodology observes a systematic approach, selection, analysis method. The result of the study is the development of a systematic series of published articles.Practical significance has the possibility of introducing the results of the study into the educational process of the specialty journalism in special and elective disciplines.